2006
DOI: 10.1590/s1678-77572006000400006
|View full text |Cite
|
Sign up to set email alerts
|

Weight loss of five commercially available denture teeth after toothbrushing with three different dentifrices

Abstract: Brushing is the most common cleansing method employed on complete dentures and it may damage the integrity of acrylic resin, the main component of this type of prosthesis. This study evaluated the abrasion resistance of artificial teeth with different number of acrylic layers, and the abrasiveness of specific and non-specific dentifrices for denture cleaning. The abrasion test was conducted by a tooth brushing device, using soft toothbrushes under load (200g). Sixty artificial teeth specimens were manufactured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
35
1
11

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(54 citation statements)
references
References 17 publications
7
35
1
11
Order By: Relevance
“…A toothbrush with soft bristles was chosen with the aim of preventing wear of the denture base or the artificial teeth, and because such brushes are readily available products, and also widely used by complete denture wearers. This is in accordance with some authors who suggest that stiff bristles that are flexible and made of nylon have low abrasivity 13,33,34 …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…A toothbrush with soft bristles was chosen with the aim of preventing wear of the denture base or the artificial teeth, and because such brushes are readily available products, and also widely used by complete denture wearers. This is in accordance with some authors who suggest that stiff bristles that are flexible and made of nylon have low abrasivity 13,33,34 …”
Section: Discussionsupporting
confidence: 93%
“…The brushes and the suspension were replaced every 50 minutes. With the replacement of the suspensions, the level of abrasion is probably higher because of the precipitation of the particles 34 …”
Section: Discussionmentioning
confidence: 99%
“…The lowest mass loss occurred for the Polident dentifrice (specific). These results are in agreement with previous studies that employed acrylic resins and artificial teeth as substrate and found that the Dentu Creme, a specific dentifrice for complete denture which contains the same abrasive system of Polident, was considered of low abrasiveness (7,9). The obtained results also showed low abrasiveness in Plexiglass acrylic (cast PMMA).…”
Section: Discussionsupporting
confidence: 92%
“…The adverse effects caused by these agents, when used as isolated method, have been reported in the literature. Thus, brushing can wear the denture base and artificial teeth (7)(8)(9)(10)(11) and hypochlorite solutions may alter color, surface roughness and flexion resistance of acrylic resins (12)(13)(14)(15). However, the interaction between both methods has not been widely investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Richmond et al 15 also confirmed the results that the abrasive potential of the dentifrices is due to the components, concentration, and size of the abrasive particles present in the dentifrice. Freitas and Paranhos 16 also stated that cleaning of dentures without dentifrices causes less surface roughness than the toothbrush with dentifrice. The results of this study are in accordance with the study by Ulusoy et al, 17 which demonstrated lower surface roughness when abrasives of the finest grit are used in the dentifrices.…”
Section: Discussionmentioning
confidence: 99%